Property rights versus public right: a study on the relationship between compulsory licensing of patents and the eminent domain doctrine in Kenya - Kiremu, Grace Wanja (Strathmore University, 2018)
Compulsory Licensing of Patents plays a significant role within Intellectual Property Law (IP Law) as a safeguard assuring public interest against the monopoly that patents grant owners. The effect of the exercise of the compulsory licensing system is an outright deprivation of a ones intellectual property right as guaranteed by the constitution. The Industrial Property Act requires that there be remuneration upon the issuance of a Compulsory License. This is similar to the requirements within Article 40, but it qualifies that compensation must be 'just and prompt.' In order to fulfil the constitutional directive, there is a well-established statutory regime under Land Regulations but the same is protection is not accorded to Patent owners subject to Compulsory Licensing. This paper seeks to compare the validity of establishing an equal legal standing between compulsory licensing and Eminent Domain. The scope of this study is limited specifically to the concept of just compensation within Land Law and Patent Law and is therefore, seeking to argue for the need of a valuation guideline to be followed in the issuance of Compulsory Licenses. It is deduced that Compulsory Licensing amounts to an exercise of the powers conferred to the state within Article 40 of the Constitution within Intellectual Property Law. It is better known as the Power of Eminent Domain. Furthermore, that there is a need to establish remuneration guidelines within IP law with many countries already having established guidelines
Submitted in partial fulfillment of the requirements of the Bachelor of Laws Degree, Strathmore University Law School
Keywords: Compulsory Licensing; Patents; Intellectual Property Law; Domain doctrine